2006
DOI: 10.1016/s1472-6483(10)62021-4
|View full text |Cite
|
Sign up to set email alerts
|

Human oocyte cryopreservation: 5-year experience with a sodium-depleted slow freezing method

Abstract: A slow freezing/rapid thawing method for the cryopreservation of human oocytes has been employed using a sodium-depleted culture media. In 53 frozen egg-embryo transfer (FEET) cycles, a 60.4% survival rate post-thaw was obtained and a 62.0% fertilization rate following intracytoplasmic sperm injection. Overall pregnancy rates were 26.4% per thaw attempt, 30.4% per patient, and 32.6% per embryo transfer. Pregnancy rates using sodium-depleted phosphate-buffered saline (PBS) as the base medium were 20.0% per thaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(72 citation statements)
references
References 30 publications
3
67
1
1
Order By: Relevance
“…The number of babies born following in vitro fertilization of cryopreserved oocytes has steadily increased over the last few years [5][6][7][8][9][10]. Much of this growth can be attributed to changes in the law in Italy, which resulted in the prohibition of embryo cryopreservation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of babies born following in vitro fertilization of cryopreserved oocytes has steadily increased over the last few years [5][6][7][8][9][10]. Much of this growth can be attributed to changes in the law in Italy, which resulted in the prohibition of embryo cryopreservation.…”
Section: Discussionmentioning
confidence: 99%
“…The resurgence of interest in human oocyte cryopreservation as a consequence of a number of reports suggesting that it may be a safe option in appropriate circumstances [1][2][3][4] has led to its clinical application and reports of a number of live births [5][6][7][8][9][10]. Although this approach has been adopted as an adjunct to routine IVF practice in Italy, this is predominantly a consequence of legal developments which resulted in the prohibition of the alternative, and more widepread, option of embryo cryopreservation.…”
Section: Introductionmentioning
confidence: 99%
“…This change halts the sperm penetration of zona and inhibits embryonic hatching, but these problems can be overcome by intracytoplasmic sperm injection and assisted hatching [27][28][29]. Several studies, however, have recently reported better post-thaw oocyte survival, fertilization, and pregnancy rates [30,31]. The incidence of chromosomal abnormalities in human embryos obtained from cryopreserved oocytes was no different from that of control embryos [32].…”
Section: Cryopreservation Of Oocytementioning
confidence: 99%
“…One main technique is slow freezing. Slow freezing gives acceptable results for human oocyte recently [30,31,64,65]. A major problem during the procedure of slow freezing is the time of exposure of oocyte to the cryoprotectants.…”
Section: Slow Freezingmentioning
confidence: 99%
“…Past clinical studies with GV oocytes from a variety of sources as well as freezing protocols have documented wide ranges for survival, maturation, fertilization, and pre-implantation development (slow-freezing: [7][8][9][10][11][12]; vitrification: [13][14][15][16]). For mature oocytes, advancements in protocols have resulted in encouraging outcomes, including slow-freezing with choline-substitution [17][18][19][20] and vitrification with the Cryoleaf system [15,[21][22][23][24]. However, there are limited prior reports of either cholinebased slow-freezing [11,25] or vitrification with the Cryoleaf [15] in human GV oocytes, with no previous assessments of spindle integrity or chromosome alignment.…”
Section: Introductionmentioning
confidence: 99%